Demokrasi Dalam Menciptakan Pemilu Bersih di Kecamatan Mungka Kabupaten Lima Puluh Kota - Rahma, Rachmawati Machriful; Rani, Rani Yohana Wati; Fitria, Fitria Aneta; Nola, Nola Nursita Erindra; Mahlil, Mahlil Adriaman (PUAN INDONESIA, 2024)
Elections are one of the pillars of democracy that enable the realization of the people's right to determine their own destiny in order to form a democratic government. Through the active participation of students, the election guard movement aims to prevent manipulation and fraud, as well as ensure that the votes of each voter are respected and counted correctly. By overseeing the implementation of general elections, the aim is to create a transparent, fair and accountable environment. As for data collection techniques through observation and interviews in an effort to create clean elections, the community in Mungka District may face several obstacles. One of them is the low level of education and political awareness in several regions. This can leave society vulnerable to manipulation and abuse by irresponsible parties. Therefore, voter education and outreach about the importance of clean elections need to be a priority. Apart from that, economic factors can also be an obstacle for society in creating clean elections. The practice of money politics and misuse of resources in campaigns often occurs in environments with high levels of poverty. Effective voter education about their rights, the electoral process, and the importance of fair participation can help reduce election abuses. Socialization of anti-corruption programs and transparency in elections is also important to encourage responsible participation from all parties.